Financial reforms and international trade - Chen, Xing; Munasib, Abdul; Roy, Devesh (International Food Policy Research Institute, 2012)
This research has been undertaken to estimate the effects of one of the major impediments to trade particularly of developing and less developed countries meaning credit constraints. In this paper we address the issue of easing of financial constraints on trade flows. Financial repression is generally a common characteristic across many developing countries. We provide evidence that financial reforms (over the period 1976–2005) significantly affected exports, in particular of industries with high external capital dependence and low asset tangibility. The coverage of reforms is comprehensive, encompassing the banking sector, interest rates, and equity and international capital markets. Our methodology improves upon existing studies by controlling for time-varying unobserved exporter characteristics.